Analysis of entropy generation on a high-lift airfoil - Davalos Ramirez, Jose Omar (2022)
In this research, an analysis of the generation of entropy in a high-lift aerodynamic airfoil with flap varying the Reynolds number, was carried out. Computational fluid dynamics was used to perform numerical flow calculations. The entropy was calculated based on the fluctuation of fluid velocity. The airfoil studied was an DLR-F15 in maximum deflection conditions. The magnitudes of were 0.5e6, 1 e6 and 5e6. The results show that increasing entropy generation increases too, and this increment occurs mainly downstream leading edge whereas in the flap was observed downstream trailing edge. The entropy generation shown the zones where aerodynamic losses occur over the airfoil and flap.